Evaluation study of treatment outcome in Tuberculosis patients receiving DOTS under RNTCP - Jain, Mayank; Swarnkar, Madhusudan; Mehta, Sathish Chandra; Kumar, Vinod (Indian Journal of Community Health, 2016)
Background: Tuberculosis is a global emergency and its control in community wholly depends on outcome of treatment taken by patient. India has 2nd position in total number of cases in World. Objective: To evaluate the factors which affect treatment outcome? Material & Methods: The study was a follow up study, for treatment outcome of tuberculosis patients receiving DOTS under RNTCP. Data were collected into SPSS version 16 and analyzed using appropriate statistical tests. Results: 241 patients were included in the study. Overall treatment success rate was 87.1%, default rate was 4.6%, failure rate was 2.1% and death rate was 6.2 %. Treatment success rate was 91.2% in category I and 70.2% in category II. Failure rate was 0.5% and 8.5%, default rate was 3.6% and 8.5%, death rate was 4.6% and 12 % for category I and category II respectively. In univariate analysis, variable education, occupation, socio-economic status, overcrowding, habit of tobacco consumption, presence of pre–existing illness and category of tuberculosis significantly affect the treatment outcome but on multiple logistic regression analysis education, occupation, habit of tobacco consumption and category of TB had significant effect on treatment outcome. Conclusion: Treatment success was 87.1% in present study conclude that DOTs is an effective form of tuberculosis treatment. Education, occupation, socio economic status and overcrowding have significant effect on treatment outcome.